THE ROLE OF DORM GUARDIANS IN OVERCOMING BULLYING BEHAVIOR THROUGH STRENGTHENING INFORMATION LITERACY AT THE MODERN ISLAMIC BOARDING SCHOOL - Maha, Jasni; Hanum, Azizah; Budianti, Yusnaili (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to 1. Analyze the forms of bullying behavior of students at the Raudhatul Jannah modern Islamic boarding school in Subulussalam city. 2. The efforts of the dormitory guardian in overcoming bullying behavior at the Raudhatul Jannah modern Islamic boarding school in Subulussalam city. 3. Obstacles of the dormitory guardian in overcoming bullying behavior of students at the Raudhatul Jannah modern Islamic boarding school in Subulussalam city. The type of qualitative research with a case study approach was used in this study. The data sources taken were from the Head of the Raudhatul Jannah Modern Islamic Boarding School, Care, dormitory guardian and students. The data collection techniques were through observation, interviews, and document studies. The results of the study showed that: (1) there was bullying behavior in Islamic boarding schools in the form of verification and non-verification before the presence of the dormitory guardian after the presence of the dormitory guardian bullying behavior had decreased significantly (2) The efforts made by the dormitory guardian to avoid bullying behavior were by facilitating students with sports facilities, creating activities, providing advice and supervising students' activities. (3) The obstacles faced by the dormitory guardian were the lack of tolerance among students, parental factors, communication, motivation and advice, and independence.